2005
DOI: 10.1002/cm.20107
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of microtubule dynamics in 3T3 fibroblasts by Rho family GTPases

Abstract: To get insight into the action of Rho GTPases on the microtubule system we investigated the effects of Cdc42, Rac1, and RhoA on the dynamics of microtubules in Swiss 3T3 fibroblasts. In control cells microtubule ends were dynamic: plus ends frequently switched between growth, shortening and pauses; the growth phase predominated over shortening. Free minus ends of microtubules depolymerized rapidly and never grew. Free microtubules were short-lived, and the microtubule network was organized into a radial array.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 44 publications
3
23
0
Order By: Relevance
“…We have previously demonstrated that, upon infection, Ad induces the formation of ''pioneer-like'' MTs at the periphery; these MTs undergo catastrophe less often, leading to more persistent MT growth and a positive drift velocity [Warren et al, 2006]. Inhibition of Rac1 by treatment of cells with 100 lM NSC23766 abrogated the Ad-induced formation of ''pioneer-like'' MTs [Warren et al, 2006], consistent with previous reports that Rac1 activation stimulates assembly of ''pioneer'' MTs [Wittman et al, 2003;Grigoriev et al, 2006]. To investigate the role of Rac1 on Ad NLE, we treated A549 cells with 100 lM NSC23766 and examined the NLE of Ad following synchronous infection.…”
Section: Efficient Ad Nuclear Localization Requires Active Rac1supporting
confidence: 88%
“…We have previously demonstrated that, upon infection, Ad induces the formation of ''pioneer-like'' MTs at the periphery; these MTs undergo catastrophe less often, leading to more persistent MT growth and a positive drift velocity [Warren et al, 2006]. Inhibition of Rac1 by treatment of cells with 100 lM NSC23766 abrogated the Ad-induced formation of ''pioneer-like'' MTs [Warren et al, 2006], consistent with previous reports that Rac1 activation stimulates assembly of ''pioneer'' MTs [Wittman et al, 2003;Grigoriev et al, 2006]. To investigate the role of Rac1 on Ad NLE, we treated A549 cells with 100 lM NSC23766 and examined the NLE of Ad following synchronous infection.…”
Section: Efficient Ad Nuclear Localization Requires Active Rac1supporting
confidence: 88%
“…Although the activity of these GTPases has not yet been assayed in our system, we know that the mutant integrin inhibits cell spreading, which is a Rac1-dependent process (26,32), and Rac1 has been shown to promote microtubule growth (54,55). Another potential integrin target is GSK-3␤, which inhibits the activity of multiple microtubule-binding proteins that promote microtubule anchorage and growth (54,(57)(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the same molecules also control polymerization dynamics of the microtubule cytoskeleton [77][78][79]. In particular Rac1 is an extremely versatile molecule that interacts specifically with numerous upstream regulators and downstream effectors [42] (Fig.…”
Section: Ros and Endothelial Cell Motilitymentioning
confidence: 98%